Transcriptomic comparison between two Vitis vinifera L. varieties (Trincadeira and Touriga Nacional) in abiotic stress conditions - Rocheta, Margarida (2016)
Background: Predicted climate changes announce an increase of extreme environmental conditions including drought and excessive heat and light in classical viticultural regions. Thus, understanding how grapevine responds to these conditions and how different genotypes can adapt, is crucial for informed decisions on accurate viticultural actions. Global transcriptome analyses are useful for this purpose as the response to these abiotic stresses involves the interplay of complex and diverse cascades of physiological, cellular and molecular events. The main goal of the present work was to evaluate the response to diverse imposed abiotic stresses at the transcriptome level and to compare the response of two grapevine varieties with contrasting physiological trends, Trincadeira (TR) and Touriga Nacional (TN). Results: Leaf transcriptomic response upon heat, high light and drought treatments in growth room controlled conditions, as well as full irrigation and non-irrigation treatments in the field, was compared in TR and TN using GrapeGene GeneChips®. Breakdown of metabolism in response to all treatments was evidenced by the functional annotation of down-regulated genes. However, circa 30 % of the detected stress-responsive genes are still annotated as «Unknown» function. Selected differentially expressed genes from the GrapeGene GeneChip® were analysed by RT-qPCR in leaves of growth room plants under the combination of individual stresses and of field plants, in both varieties. The transcriptomic results correlated better with those obtained after each individual stress than with the results of plants from field conditions. Conclusions: From the transcriptomic comparison between the two Portuguese grapevine varieties Trincadeira and Touriga Nacional under abiotic stress main conclusions can be drawn: 1. A different level of tolerance to stress is evidenced by a lower transcriptome reprogramming in TN than in TR. Interestingly, this lack of response in TN associates with its higher adaptation to extreme conditions including environmental conditions in a changing climate; 2. A complex interplay between stress transcriptional cascades is evidenced by antagonistic and, in lower frequency, synergistic effects on gene expression when several stresses are imposed together; 3. The grapevine responses to stress under controlled conditions are not fully extrapolated to the complex vineyard scenario and should be cautiously considered for agronomic management decision purposes